2012
DOI: 10.1136/sextrans-2012-050557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and other sexually transmitted infections and factors associated with syphilis among female sex workers in Panama

Abstract: ObjectivesBiological and behavioural surveillance of HIV and sexually transmitted infections (STIs) among populations at highest risk have been used to monitor trends in prevalence and in risk behaviours. Sex work in Panama is regulated through registration with the Social Hygiene Programme, Ministry of Health. We estimated prevalence of HIV and STIs, and factors associated with active syphilis among female sex workers (FSWs).MethodsA cross-sectional study using venue-based, time-space sampling was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
(10 reference statements)
1
19
1
Order By: Relevance
“…The population of Chinese residents in Panama is estimated at 102,000 individuals, representing 2.9-3.1% of the total population. In this study, we found a high prevalence of HBV in the Chinese community in Panama City, approximately 13.1%, which is comparable to the prevalence in high endemic areas of China (Zeng et al 2005) and is 20 times higher than the observed prevalence in female sex workers in Panama (Hakre et al 2012). A similar phenomenon has been observed in other cosmopolitan areas around the world (Merican et al 2000, Pollack et al 2006 , Khan et al 2008).…”
Section: Discussionsupporting
confidence: 47%
“…The population of Chinese residents in Panama is estimated at 102,000 individuals, representing 2.9-3.1% of the total population. In this study, we found a high prevalence of HBV in the Chinese community in Panama City, approximately 13.1%, which is comparable to the prevalence in high endemic areas of China (Zeng et al 2005) and is 20 times higher than the observed prevalence in female sex workers in Panama (Hakre et al 2012). A similar phenomenon has been observed in other cosmopolitan areas around the world (Merican et al 2000, Pollack et al 2006 , Khan et al 2008).…”
Section: Discussionsupporting
confidence: 47%
“…In Panama, HBV prevalence rates vary according to the population being studied. Commercial sex workers (CSW) show a low prevalence (0.9%) [ 3 ]; men that have sex with men (MSM) have an intermediate prevalence (3.4%) [ 4 ], while blood donors have the lowest prevalence (0.03%) [ 5 ]. These differences in HBV prevalence between the different groups has also been observed in other countries [ 6 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variables with p<0.20 in univariate analysis were included in the logistic regression model in order to assume that potential confounders were not excluded from the analysis. This cutoff for eligibility in the multivariate analysis has been also selected in previous studies with similar proceedings for data analysis [23][24][25]. Those with p<0.05 were retained in the final multivariate logistic model in a backward stepwise manner, and were considered as independently associated with AUD.…”
Section: Discussionmentioning
confidence: 99%